Diseño de una desbastadora de probetas para la realización de prácticas de metalografía. - Agualongo Caguana, Alexis David (2021)
Design of metallographic grinding machine is carried out due to the needs that students have when carrying out laboratory practices in the mechanical workshop of the Technical University of Cotopaxi of the Electromechanical Engineering Career in order to shorten sample preparation time due to the quantity of students who receive this subject and short hours of class. The objective of making this design is to have a compact system which is functional and useful as long as they meet the operating requirements such as the forces to be applied in the roughing process, the revolutions which the sandpaper bands will work, the system of refrigeration and the drainage system since those parameters that will act directly with the sample in this way the operation will be ideal for an optimal and precise roughing process. This will be achieved with the application of technical regulations for the preparation of metallographic samples in addition to a design criterion which will help for the selection and implementation of commercial accessories that can be acquired in the market which will be attached in an appropriate way to the design, taking The respective design calculations are taken into account, since from these the selection of each element that will make up the proposed system will be made. With the above, a compact and functional design is established based on the ASTM E3 standard, which establishes the parameters that the design must meet with the application of calculations and CAE analysis, which will help to verify the efficiency of the metallographic grinder proposal.